Mapping Cilento: Using geotagged social media data to characterize tourist flows in southern Italy. (December 2016) - Chua, Alvin; Servillo, Loris; Marcheggiani, Ernesto; Moere, Andrew Vande
Abstract: New sources of geotagged information derived from social media like Twitter show great promise for geographic research in tourism. This paper describes an approach to analyze geotagged social media data from Twitter to characterize spatial, temporal and demographic features of tourist flows in Cilento - a regional tourist attraction in southern Italy. It demonstrates how the analysis of geotagged social media data yields more detailed spatial, temporal and demographic information of tourist movements, in comparison to the current understanding of tourist flows in the region. The insights obtained from our case study illustrate the potential of the proposed methodology yet attention should be paid to biases in the data as well as methodological limitations when drawing conclusions from analytical results. Highlights: We introduce a novel approach to tourist flow analysis based on geotagged social media data. This approach is useful for studying the spatial, temporal and demographic features of tourist flows. We show the advantage of our approach through an analysis of tourist movement in South Italy.